2007
DOI: 10.1007/s00213-007-1001-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increased serotonergic activity on human sensory gating and its neural generators

Abstract: In the current study, escitalopram did not affect P50 suppression in healthy male volunteers, which indicates that sensory gating is not affected by a nonspecific increase in serotonergic activity. Furthermore, a generator with a fronto-central location in the brain (possibly the anterior cingulate) was found to be the primary source of the P50 evoked potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
(59 reference statements)
3
21
0
Order By: Relevance
“…Thus, frontal medial gyrus may play a role in automatically alerting inactive co-twins more than the active co-twins of deviant information ascending from the body. Sensory gating using different electrical stimulation paradigm has been applicably studied in psychiatry where source modeling has implicated frontal medial gyrus as an important player in gating (Bak et al 2011;Jensen et al 2008). Thus it may be that amplitude differences we have observed are explained by differences in sensory gating emerging from different levels of physical activity.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, frontal medial gyrus may play a role in automatically alerting inactive co-twins more than the active co-twins of deviant information ascending from the body. Sensory gating using different electrical stimulation paradigm has been applicably studied in psychiatry where source modeling has implicated frontal medial gyrus as an important player in gating (Bak et al 2011;Jensen et al 2008). Thus it may be that amplitude differences we have observed are explained by differences in sensory gating emerging from different levels of physical activity.…”
Section: Discussionmentioning
confidence: 86%
“… 21 , 22 , 23 , 157 , 159 These and other studies have shown, however, that additional brain regions are also significant sources of P50 gating in the human brain. Gating generators may include the thalamus, 23 , 158 , 160 superior temporal gyrus/auditory cortex, 161 , 162 , 163 , 164 , 165 , 166 medial frontal cortex, 22 , 162 , 163 , 167 , 168 dorsolateral prefrontal cortex, 21 , 158 , 159 , 169 ventrolateral prefrontal cortex 160 and insula. 22 , 160 , 161 Animal studies have found additional gating generators in the medial septum, 170 thalamus, 64 striatum, 171 amygdala 172 and medial prefrontal cortex.…”
Section: Methodological Effects and Considerationsmentioning
confidence: 99%
“…All subjects were examined with the Copenhagen Psychophysiology Test Battery (CPTB) Jensen et al, 2008;Wienberg et al, 2010). The CPTB includes PPI, P50 suppression, mismatch negativity (MMN), and selective attention paradigms.…”
Section: Psychophysiologymentioning
confidence: 99%